2012
DOI: 10.1074/jbc.m111.273052
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Membrane-bound Variant of Metalloendopeptidase Neurolysin (EC 3.4.24.16) as the Non-angiotensin Type 1 (Non-AT1), Non-AT2 Angiotensin Binding Site

Abstract: Background: Angiotensin II, the renin-angiotensin system effector peptide, interacts with a recently discovered binding site that is distinctly different from its classic receptors. Results: A radioiodinated angiotensin II photoprobe bound to a ϳ75-kDa membrane protein, enabling its isolation and identification. Conclusion: Membrane-bound metalloendopeptidase neurolysin (EC 3.4.24.16) is the novel angiotensin-binding protein.Significance: This metalloendopeptidase may be a crucial component of the renin-angiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 63 publications
2
37
0
Order By: Relevance
“…As shown in Figure 1, optimal unmasking was observed at PCMB concentrations of 100–300 μM. The optimal PCMB concentration are slightly lower than our initial report [26], but is consistent with subsequent more recent studies [33,56]. Two-way ANOVA of the K D values indicated that the K D for testis was lower at 100 μM than at 300 μM (p<0.01) and that there was a main effect of higher affinity at 100 μM versus 300 μM (p=0.0033).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…As shown in Figure 1, optimal unmasking was observed at PCMB concentrations of 100–300 μM. The optimal PCMB concentration are slightly lower than our initial report [26], but is consistent with subsequent more recent studies [33,56]. Two-way ANOVA of the K D values indicated that the K D for testis was lower at 100 μM than at 300 μM (p<0.01) and that there was a main effect of higher affinity at 100 μM versus 300 μM (p=0.0033).…”
Section: Resultssupporting
confidence: 91%
“…Of primary interest for assessment of the PCMB activation of 125 I-SI Ang II binding is whether PCMB mimics naturally occurring physiological or pathophysiological conditions. While these studies were in progress, we determined that this potential new member of the RAS was a membrane associated variant of neurolysin (E.C.3.4.24.16) based upon studies in neurolysin transfected cells and neurolysin knockout mouse brains [33]. Neurolysin has a broad tissue distribution [49] and is highly expressed in rat testis membranes as well as the brain [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests the existence of a non-AT 1 , non-AT 2 , non-neurolysin Ang II binding site with a different pattern of expression in the mouse brain. A much smaller amount of 125 I-SI Ang II binding (∼17% that of the wild-type strain) was observed in our previous study using membrane homogenates obtained from the brains of neurolysin knockout mice [40]. A possible explanation for this disparity may be the differences in tissue preparation.…”
Section: Discussionmentioning
confidence: 58%
“…In neurons, but not astrocytes, approximately 10 % of the enzymatic activity is membrane-bound [59]. Wangler et al [60] report that “membrane- anchoring mechanism (s)” are not understood. Clearly, analytical techniques with the objective of measuring membrane-bound (ecto) enzyme activity would be useful.…”
Section: Introductionmentioning
confidence: 99%